Sarthaks APP
0 votes
753 views
in Mathematics by (7.5k points)
edited by

If x= 2(sq.rt of 2 + sq.rt of 6)/3{sq.rt of(2+sq.rt of 3)} then simplify x to get x as a rational number.

Please log in or register to answer this question.

1 Answer

+1 vote
by (692 points)

\(=\frac{2(\sqrt 2+\sqrt 6)}{3\sqrt{2+\sqrt 3}}\)

\(=\frac{2(\sqrt 2+\sqrt 6)}{3\sqrt{2+\sqrt 3}}\times \frac{\sqrt {2-\sqrt 3}}{\sqrt{2-\sqrt 3}}\)

\(=\frac{2(\sqrt 2+\sqrt 6)\times \sqrt{2-\sqrt 3}}{3\sqrt{4-3}}\)   \((\because (a+b)(a-b)=a^2-b^2)\)

\(=\frac{2}{3}\left(\sqrt{(2-\sqrt 3)\times (\sqrt 2+\sqrt 6)^2}\right)\)

\(=\frac{2}{3}\sqrt{(2-\sqrt 3)(2+6+4\sqrt 3)}\)

\(=\frac{2}{3}\sqrt{16-8\sqrt 3+8\sqrt 3-12}\)

\(=\frac{2}{3}\sqrt 4\) \(=\frac{2}{3}\times 2\) \(=\frac{4}{3}\).

Sarthaks APP

Welcome to Sarthaks eConnect: A unique platform where students can interact with teachers/experts/students to get solutions to their queries. Students (upto class 10+2) preparing for All Government Exams, CBSE Board Exam, ICSE Board Exam, State Board Exam, JEE (Mains+Advance) and NEET can ask questions from any subject and get quick answers by subject teachers/ experts/mentors/students.

Categories

...